Engineering of Dihydroxy Biphenyl Dioxygenase Enzyme to Improve Its Performance In Removing PCBs: A Molecular Docking Study - Susan Yazdankhah; Alireza Zakeri; Saeed Khalili; Abolfazl Jahangiri; ZahraalSadat Hashemi; Alireza Heidari (مجله علمی دانشگاه علوم پزشکی کردستان)
Background and Aim: Polychlorinated biphenyls (PCB) industrial pollutants are one of the most important environmental pollutants whose removal is very important. PCBs are degraded biologically by several enzymes and in a multi-step process. One of these enzymes is called DHBD (2,3-dihydroxy biphenyl 1,2-dioxygenase) and is encoded by the BphC gene. Enhancing the function of the enzyme and reducing the binding affinity of the enzyme to the inhibitor (tert-butanol) will improve the function of the enzyme and increase its efficiency. This research has been carried out in bioinformatics to strengthen the enzyme and weaken the inhibitory effect through mutation in the amino acids of the active site. Materials and Methods: The amino acid sequence of the enzyme was obtained from the UniPprot database and to check similar sequences with PSI-BLAST method, similar sequences were searched from close to distant protein species. By performing multiple alignments of PSI-BLAST sequences, 250 sequences were matched. The results of sequencing the amino acids of the active site showed that some sites have variable amino acids and were used as candidates for mutagenesis. The position of the T-Butanol inhibitor was simulated using DISCOVERY software. Results: By molecular docking with PYRX software between the wild enzyme and the substrate, the binding energy -6.2 Kcalmol-1and for the candidates of mutations resulting from the alignment, Phenylalanine 201 to Threonine (6. 9 Kcalmol-1) and Threonine 280 to serine (6. 8 Kcalmol-1) Calculated. Conclusion: The more negative binding energy indicates the greater stability of this interaction in the mutant enzyme. As a result, these mutations will be able to improve the strength of the enzyme function. The simulation of the position of the inhibitor and the starting material in the enzyme showed that the distance of the inhibitor from the active site and the starting material is likely to be favorable if the interaction of the inhibitor on the amino acids of the active site is reduced and as a result, the binding stability of the biphenyl starting material with the enzyme is increased. Decreasing the inhibitory power will increase the catalytic power of the enzyme in the destruction of PCBs.